Transfer of Land Rights in Company Entry (Inbreng) at the South Jakarta City Land Office - Luthfiyah, Laily (CV. Strata Persada Academia, 2024)
This study aims to understand the phenomenon known as inbreng, which refers to the practice of transferring land rights as income within a firm. The corporation is structured as a limited liability company. The land is the purpose of the company's operations in this scenario. By using a juridical-normative method and statutory and conceptual approach, as well as through a literature review of secondary data, this research found that when it comes to a firm, the procedure of transferring land rights as income can be extremely lengthy and involves multiple steps. Starting from reducing land rights if the land status is private property, based on holding a GMS related to land acquisition, then through appraisal, paying taxes, followed by making a Company Entry Deed by Land Titles Registrar (LTR), ending with the land registration process at the South Jakarta Land Office. So far, the implementation of the transfer of land rights at the South Jakarta Land Office has been carried out in accordance with applicable procedures and regulations.